The effect of using social media and fear of missing out on emotional wellbeing in children in the digital age - Mujazi, Mujazi; Fadli, Muhammad Rijal; Rosyid, Ainur; Hapudin, Muhammad Soleh; Rosidi, Moh. Imron; Afwan, Bahtiar (Intelektual Pustaka Media Utama, 2025)
In today's digital age, social media (SM) offers convenient access to information, social connections, and various content. Nonetheless, the utilization of SM and the fear of missing out (FOMO) phenomenon profoundly influence children's emotional wellbeing (EW). This study seeks to investigate the impact of SM usage and FOMO on children's EW in the digital era. Employing a quantitative approach, the research involves elementary school students in Jakarta, Indonesia. Cluster sampling was utilized to select a sample of 265 students. Data collection was conducted through a questionnaire designed to capture relevant variables. Analysis was performed using structural equation modeling (SEM) facilitated by the SMART-PLS 3.0 software. Findings revealed a significant significance value of 0.000 (0.0000.05), indicating that SM usage and FOMO have a positive and noteworthy effect on children's EW in the digital era. This study offers valuable insights for parents, educators, and child psychologists regarding the influence of SM on children's EW, thereby facilitating the formulation of more effective educational guidelines and strategies to assist children in managing their EW in the digital era.